Pannonische Glanztonware aus dem Auxiliarkastell von Carnuntum Ausgrabungen der Jahre 1977-1988 - Adler-Wölfl, Kristina (Österreichisches Archäologisches Institut, 2004)
The "Pannonische Glanztonware" (PGW) is a type of ceramics, which was wide-spread in Pannonia from the end of the 1st well into the 3rd century A.D. It is a product of local potteries, in which the influence of ceramics in the La Tène tradition and of imported Roman ceramics joined to create a new, typical Pannonian ware. In the PGW was produced exclusively table ware. The shapes of the vessels are to a large extent taken over from the Terra Sigillata resp. influenced by it; some of them also show the influence of the raetic-germanic area and the local utility ware. The vessels have a fine paste, a slip and are fired at the beginning of production, in most cases in a reducing atmosphere. But from the beginning oxidized fired pieces also appeared; their portion is - regionally scattered - increasing in the 3rd century. A number of the vessels are decorated in a for typical PGW way with stamps either inside at the base or outside; most of them, however are undecorated. The basis of the investigations into the PGW are the finds, which were unearthened at the excavations 1977-1988 conducted by H. Stiglitz in the auxiliary fort of Carnuntum. The finds of the "Steinkastell I" and the over it lying levelling layer give a representative view of the PGW in the second third of the 2nd century in the area of Carnuntum. On the basis of the finds published here, a open classification-system was created, so that it can be expanded with further finds, which are until now only known from unpublished locations or from other publications. Regarding the material of the vessels five fabrics ("STyp 1-5") and four types of slip ("ÜTyp A-D") could be distinguished. Petrographic and heavy mineral analysis, which were carried out by R. Sauer, showed that the vessels of fabric 2, 3 and 5 were probably produced in the area of Carnuntum. Apart from the emphasis on north-western Pannonia, which results from the basis of the finds of Carnuntum, a summary is given of the spectrum of the PGW, the potter's stamps, workshops and finds from dated locations in eastern and south-western Pannonia. A short discourse on the stamped ceramics found in south-eastern Pannonia, Moesia and Dacia completes the picture.